Implementasi Manajemen Pengendalian Mutu Sekolah - Indraswati, Dyah; Widodo, Arif (Universitas Negeri Surabaya, 2021)
The purpose of this research is to describe the implementation of school quality control management at SMK N 2 Karanganyar, Surakarta, Central Java. This research uses a qualitative descriptive approach. Data collection techniques are carried out with interviews, observations, and documentation. Indicators developed by researchers as guidelines in data collection include school planning, school program implementation, principal leadership, and supervision and evaluation. Data analysis techniques include data reduction, data presentation, and inference. The education process at SMK N 2 Karanganyar has met the quality education criteria which include: 1) the effectiveness of the headmaster's leadership; 2) active participation of all interested components in the school; 3) effectiveness of teaching and learning process; 4) relevant curriculum; 5) directed vision, mission, and objectives; 6) conducive to the climate and school environment; 6) community involvement and parents of learners. This research implies that the headmaster's leadership and managerial ability are necessary to realize effective school management. The quality of education at SMK N 2 Karanganyar has the opportunity to be dynamically and innovatively devised to achieve improved standard quality.Â